Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524840 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524840 10.53832/edtechhub.0047 2339240:LSC89UVX 2339240:RIE9TWUK 2339240:SI398B6V 2405685:54BCQ23M 2405685:6NNCFPHE 2405685:77NJVUB6 2405685:HUY7VUM6 2405685:VTQDT65R 2405685:WFDCC7KZ 2534378:BQ8BJBGF
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Reflections on technology, teaching, learning, and professional development: Findings from a teacher survey in Tanzania - Koomar, Saalim; Hennessy, Sara; Zubairi, Asma; Kindoli, Robert; Kreimeia, Adam (African Educational Research Journal, 2022)
This paper presents findings from a survey of 774 government school teachers across Tanzania over the period 2020-2021. The aims were to capture teachers' recent experiences concerning (1) access and use of technology; (2) any student learning losses observed, and teachers' recommendations to address lost learning; and (3) experiences and needs concerning teacher professional development (TPD). Key findings were (1) forty percent of teachers reported that their school lacked access to any form of technological device, with almost half stating they never used digital technologies for teaching and learning purposes. (2) Almost half of the teachers perceived that girls' learning suffered more than boys, and more than 60% of teachers believed learners from the financially poorest households suffered the greatest learning losses. (3) Teachers in Tanzania engaged in very little TPD and wanted increased support. The key differences across teacher groups were further examined by demographic factors, with notable differences apparent between urban and rural teachers, teachers with different levels of experience and different qualification levels. Recommendations are presented to stakeholders across the education ecosystem, including policymakers, school leaders, TPD designers, teachers, and researchers. The findings inform a national technology-mediated TPD programme in Tanzania.
Publisher: Net Journals ERIC Number: EJ1373064 KerkoCite.ItemAlsoKnownAs: 10.30918/AERJ.104.22.048 10.5281/zenodo.5863400 10.53832/edtechhub.0097 2339240:6EFQH53V 2339240:7QAZINAG 2405685:49EBMKRI 2405685:GXZHRRYW 2405685:YXFLNITE
Keywords: Access to Computers; Elementary School Teachers; Faculty Development; Foreign Countries; Gender Differences; Learning Processes; Pedagogical Content Knowledge; Poverty; Public School Teachers; Rural Urban Differences; Secondary School Teachers; Social Differences; Teacher Attitudes; Teacher Characteristics; Teacher Qualifications; Teacher Surveys; Teaching Experience; Teaching Methods; Technological Literacy; Technology Integration; Technology Uses in Education; _r:AddedByZotZen

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7677950 ZenodoArchiveConcept: 7677949 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7677950 10.53832/edtechhub.0157 2339240:RBNTBT7Z 2405685:9WBV8KPN 2405685:EGL4QHDZ
Keywords: _r:AddedByZotZen

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0080 2339240:PRMHXVPE 2405685:7S9CUP77 2405685:HHXQI3S4 2405685:VU5JQKWG 2534378:BXN59IRN
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Exploring Teacher Digital Skills and Literacy Competencies: A curated list of frameworks and resources to inform UNICEF Thailand - Flam, Rebekka; Upadhyay, Arjun; Thang, Sarah (EdTech Hub, 2025)
This report was developed in response to a request from UNICEF Thailand for a curated list of digital skills and literacy frameworks designed for teachers. It reviews and compares 16 global, regional, and national frameworks to inform the development or adaptation of teacher-specific training and materials in Thailand. Key insights include the multidimensional nature of digital literacy, the central role of teacher development, and the alignment of learner-centred approaches with competency-based education (CBE). The report concludes with practical recommendations for policymakers, educators, and practitioners in Thailand involved in designing or implementing digital skills and literacy frameworks. Keywords: Digital literacy; digital skills frameworks; teacher competencies; Thailand; Southeast Asia; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15499486 ZenodoArchiveConcept: 15499485 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1120 2405685:I2DINV6N
Keywords: _r:AddedByMyEducationEvidence

Position paper: Using EdTech to support teacher education and professional development in low- and middle-income countries (internal working paper). - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2020)
ZenodoArchiveID: 5652080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652080 2339240:VJNSF4EV 2339240:Z6ZIBS2B 2405685:6E2K4GGE
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
ZenodoArchiveID: 5652042 _eprint: https://bera-journals.onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13114 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13114 10.5281/zenodo.5652042 2339240:ELI3E5RF 2339240:TJNJX997 2405685:3KJJW6XZ 2405685:9V69ZAFP 2405685:BDG6N6PJ 2405685:JE8I8566 2405685:YY7LXWQB
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

Using evidence to strengthen tech-supported teacher professional development in Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4585511 10.5281/zenodo.4728170 2405685:G2SH3FP6 2405685:HLMSBECU 2405685:MKH2ZP2T 2405685:TYXJSKEP
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _r:AddedByZotZen; _zenodoETH

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
ZenodoArchiveID: 5652007 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652007 2405685:KZ6FTNMC
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

Effective Teacher Education in Low-Connectivity Settings: A Curated Resource List - Koomar, Saalim; Allier-Gagneur, Zoé; McBurnie, Chris (EdTech Hub, 2020)
This list curates resources — both tools and initiatives — that can be adapted to support teacher education in low-connectivity settings, a prevailing challenge in Madagascar. Each example identifies the challenges; necessary prerequisites; pros and cons and; costs and impact assessment data where possible.
ZenodoArchiveID: 5652141 previousDOI: 10.5281/zenodo.4762283 previousDOI: 10.5281/zenodo.4762283 2405685:UQSMRFBF previousDOI: 10.5281/zenodo.3407498 EdTechHub.Source: DOI: DOI:10.5281/zenodo.4762283 2405685:UQSMRFBF EdTechHub.Source: <this> shortDOI: 10/ghgnd8 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3407498 10.5281/zenodo.5652141 10/ghgnd8 2129771:U3XSZB5F 2339240:CRCGCNE9 2405685:UQSMRFBF
Keywords: C:Madagascar; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; W:Low connectivity and/or electricity; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
ZenodoArchiveID: 5652135 previousDOI: 10.5281/zenodo.3906041 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906041 10.5281/zenodo.5652135 2339240:546TH9C9 2339240:E5AXYSMF 2339240:RKVKV84H 2405685:4ER9WB55 2405685:7JSP4PFC 2405685:DMSLLEQV 2405685:HZ5X5A4W 2405685:V44Z75Z3 2405685:VVB3BRE5
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?” As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Library Catalog: edtechhub.org Section: general shortDOI: 10/ghgk6c KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3690149 10/ghgk6c 2339240:6LUYX6ZR 2339240:AS8A9UGV 2405685:CV2HG6CJ 2405685:FI72KCVG 2405685:JTA347FP 2405685:N2YMVN4S 2405685:TEVH3TNS
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Teacher Retention and Mobility in Sierra Leone: What factors motivate teachers to stay at or leave schools? - Lurvink, Anne-Fleur; Mansaray, Kabiru; Kamara, Josephine; Khanu, Alimamy James; Cameron, Emma; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
The current study is the third in a series of research studies, which aim to generate evidence that can support the MBSSE and TSC with their teacher allocation and deployment strategy. Our first study investigated teacher preferences for school choice and uncovered important considerations for teacher deployment. Following this, we investigated mobility patterns for teachers who are on the government payroll, and payroll teacher retention rates. The latter study helped us understand where teachers move to when they change schools, and also helped us identify areas with high (hot spots) and low retention rates (cold spots). The current study is explanatory in nature and aims to understand why teachers stay at or leave their schools. Keyword: teacher allocation; teacher retention; teacher mobility; Sierra Leone An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7966434 ZenodoArchiveConcept: 7966433 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7966434 10.53832/edtechhub.0168 2405685:CQ8JNCH8
Keywords: _r:AddedByZotZen

EdTech Initiatives Focused on Classrooms and Teachers: A Curated List for Rwanda - Chuang, Rachel; Koomar, Saalim (EdTech Hub, 2020)
This document was produced in response to a request from the FCDO Rwanda team for a curated list of EdTech initiatives related to the following focus areas: 1. Classroom software 2. Teacher education 3. School administration.
ZenodoArchiveID: 4762316 previousDOI: 10.5281/zenodo.4050155 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4762316 10.5281/zenodo.3990369 10.5281/zenodo.4050155 10.5281/zenodo.4762316 10/ghgk62 2339240:86AAWUD3 2339240:BMRM6MNQ 2339240:RYU57YK3 2405685:BMDY65UF 2405685:CHX3W9RE 2405685:WGYWI78R
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

What Should Ministries of Education Prioritise When Crafting Their Edtech Strategies? - Thinley, Sangay (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at priorities for governments and ministries of education when crafting EdTech Strategies. Interest in developing EdTech strategies related to operational targets and outcomes has increased over the past few years, especially in response to the learning disruptions caused by the Covid-19 pandemic. Evidence suggests that countries with established EdTech strategies were better equipped to respond to the pandemic and its effects due to their advanced preparation and readiness for large-scale remote learning. We examine the key principles for EdTech strategies, including the importance of focusing on learning outcomes, inclusivity, teacher training, costs, and contextual needs, among other factors. We draw on EdTech Hub's work in supporting several governments in designing and implementing EdTech strategies, as well as broader evidence from the field, to offer practical insights. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt, such as prioritising consultative processes of strategy development while focusing on multi-modal, problem-driven EdTech solutions and interventions guided by a unifying educational goal. We highlight areas that require further research, in particular questions related to cost-effective approaches to improving global learning, how governments can develop dynamic and iterative strategies, and the role of private sector partnerships in the successful implementation of EdTech strategies. Keywords: EdTech; education technology; education strategy; best practices for EdTech; EdTech planning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13360175 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1054 ZenodoArchiveConcept: 13360174
Keywords: _r:AddedByMyEducationEvidence

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10610797 ZenodoArchiveConcept: 10610796 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1007 2339240:SZE9FBW4 2405685:IIAMD77T
Keywords: _r:AddedByMyEducationEvidence

How can messaging apps, WhatsApp and SMS be used to support learning? A scoping review - Jordan, Katy (Technology, Pedagogy and Education, 2023)
In response to disruption to education during the Covid-19 pandemic, mobile phone-based messaging has emerged in some instances as an accessible, low-connectivity way of promoting interactivity. However, no recent reviews have been undertaken in relation to how social media and messaging apps can be used to effectively support education in low- and middle-income countries. In this scoping review, 43 documents were identified for inclusion and three main thematic areas emerged: supporting student learning (including interacting with peers and other students, peer tutoring and collaborative learning; and interacting with teachers, through content delivery, teaching and assessment); teacher professional development (including structured support and prompts, and informal communities of practice); and supporting refugee education. The discussion and findings are both of practical use, to inform responses to the current pandemic and designing initiatives in the future, and will also be useful for advancing research in this expanding field.
Accepted: 2022-05-18T23:30:06Z Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.17863/CAM.84697 2405685:8XW8JR6H

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707910 2405685:7HCBSU4P
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

L'utilisation des preuves pour renforcer la formation pédagogique à travers les technologies à Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4645807 10.5281/zenodo.4728174 2405685:552YTW72 2405685:BBWJNPNA
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodoETH

Structured Pedagogy and EdTech - Adam, Taskeen; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2021)
ZenodoArchiveID: 4460344 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4460344 2129771:DDU3QPXM 2339240:5XNMEGSN 2339240:XIRCF4HG 2339240:XXL72KUQ 2405685:2QM825CH 2405685:5RMUBA3Q 2405685:GBS5KW7S
Keywords: _EdTechHub_Output; _MELA_seen; _coming soon; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode

Open Education Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (Zenodo, 2020)
This curated list defines open educational resources, offers background on open source licensing, and provides a review of OER relevant to the context of Ghana in response to an EdTech Hub helpdesk request. This document does not intend to set out a comprehensive list of OER used by teachers, students, parents or other stakeholders; rather, this document will identify exemplars of OER provided they are relevant to the Ghanaian context and focus on: reaching marginalised learners through offline or online content; reaching marginalised learners through mass media; using OER for teacher education; further useful resources and methods of implementing OER.
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3906041 10.5281/zenodo.3906041 2339240:35NW4SYR 2405685:VD8J4NCU

The Use of Technology in the CPD Implementation Plan in Tanzania - Adam, Taskeen; El-Sefary, Yomna; Haßler, Björn; Khalayleh, Abdullah; Kremeia, Adam; Proctor, Jamie; Mtebe, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4665846 2405685:N5HMII3R
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

EdTech for Special Educational Needs and Disabilities in Malawi: Setting the Research Agenda - Plaut, Daniel; Pitchford, Nicola; Humphrey, Catherine (2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13907321 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1067 ZenodoArchiveConcept: 13907320
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987889 ZenodoArchiveConcept: 10987888 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1006 10.53832/edtechhub.1023 2339240:U7UE5PIN 2405685:B422KBGQ 2405685:HD58IXI3 2405685:PGRMI8NH
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652140 previousZenodoArchiveID: 3936687 previousshortDOI: 10/ghgnd2 previousDOI: 10.5281/zenodo.3936687 shortDOI: 10/ghgnd2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3936687 10.53832/edtechhub.0037 10/ghgnd2 2339240:EHTSKIBR 2339240:YQHNWNMB 2405685:5P5HVP47 2405685:BBP57X2K 2405685:SKFMQF3F 2405685:XI5PXVB3
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652130 previousZenodoArchiveID: 3830953 previousshortDOI: 10/ghgk68 previousDOI: 10.5281/zenodo.3830953 shortDOI: 10/ghgk68 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3830953 10.53832/edtechhub.0033 10/ghgk68 2339240:XCBTX2XL 2405685:2HM2SBVM 2405685:FU7Z8QM7
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen

Conseils pour l’introduction de la technologie en classe Liste de sources annotée - Allier-Gagneur, Zoé; Lwamba, Etienne (EdTech Hub, 2020)
Cette liste de sources annotée a pour but d’informer la prise de décisions des acteurs du domaine de l’éducation concernant l’introduction de technologies en classe dans les pays à revenu faible et intermédiaire. Cette liste est une introduction qui expose de façon informelle certains des conseils généraux que prodiguent souvent les experts de l’EdTech Hub.
ZenodoArchiveID: 3952001 previousDOI: 10.5281/zenodo.3952001 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3952001 10.53832/edtechhub.0024 2339240:6H2ZA568 2405685:HDRVT5N4 2405685:PA2H8NGA
Keywords: F: Helpdesk response; LP: French; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

National EdTech strategies: what, why, and who - Chuang, Rachel; Coflan, Caitlin; Giraldo (UNICEF), Juan-Pablo; Attfield (FCDO), Ian; Tungatarova (UNICEF), Auken; Tungatarova (UNICEF), Caitlin Coflan, Juan-Pablo Giraldo (UNICEF), Ian Attfield (FCDO) and Auken, Rachel Chuang (EdTech Hub, 2022)
Using evidence from Covid responses, the report advises policymakers responding to learning loss caused by the pandemic to use existing EdTech, and focus on good pedagogy that is supported, rather than replaced by, technology.
KerkoCite.ItemAlsoKnownAs: 2339240:G82EPYXB 2405685:MKLN5KM6

National EdTech strategies: what, why, and who - Chuang, Rachel; Coflan, Caitlin; Giraldo (UNICEF), Juan-Pablo; Attfield (FCDO), Ian; Tungatarova (UNICEF), Auken; Tungatarova (UNICEF), Caitlin Coflan, Juan-Pablo Giraldo (UNICEF), Ian Attfield (FCDO) and Auken, Rachel Chuang (EdTech Hub, 2022)
Using evidence from Covid responses, the report advises policymakers responding to learning loss caused by the pandemic to use existing EdTech, and focus on good pedagogy that is supported, rather than replaced by, technology.
KerkoCite.ItemAlsoKnownAs: 2339240:G82EPYXB 2405685:MKLN5KM6